Performance in adolescents of the two Japanese serum creatinine based estimated glomerular filtration rate equations, for adults and paediatric patients: A study of the Japan Renal Biopsy Registry and Japan Kidney Disease Registry from 2007 to 2013. Issue 6 (June 2017) - Uemura, Osamu; Yokoyama, Hitoshi; Ishikura, Kenji; Gotoh, Yoshimitsu; Sato, Hiroshi; Sugiyama, Hitoshi; Honda, Masataka; Matsuo, Seiichi
Abstract: There are two different Japanese serum creatinine‐based equations for estimated glomerular filtration rate (eGFR), for adults and paediatric patients, with both equations deemed applicable to 18‐year‐old subjects. This study assessed the relative accuracy of the two equations in assessing eGFR in patients aged 18 years with chronic kidney disease. A total of 3042 patients (1679 males and 1363 females), aged 2–20 years, who were registered in the Japan Renal Biopsy Registry or the Japan Kidney Disease Registry between 2007 and 2013 were evaluated. eGFR values derived from formulas for children (Uemura's formula) and adults (the 3‐variable Japanese formula) were calculated and compared, especially in patients aged 18 years. At all ages, but especially at younger ages, eGFR was significantly higher when calculated with the adult than the paediatric formula. This finding was also observed in 18‐year‐old adolescents with eGFR <90 mL/min per 1.73 m 2 ( P  = 0.026). However, the mean difference between the two calculated eGFRs was only 2.79 mL/min per 1.73 m 2 . These findings indicate that both creatinine‐based equations used to calculate eGFR rate in Japanese children and adults with chronic kidney disease could be used to determine eGFR in 18‐year‐old subjects, with the difference between the two within permissible levels for clinical use.